The Concept Of Legal Regulation Of Soe Restructuring Through Holding Mechanism - Prasetyo Kartiadi; Kusbianto Kusbianto; Rilawadi Sahputra (International Asia Of Law and Money Laundering, 2023)
Given the contribution of state-owned enterprises that need to be increased enough, to improve and empower massively several sectors in the state-owned companies, restructuring must be accommodated. Thus, the restructuring of state-owned enterprises with formation of holding companies for each sector has been planned by the government, which is the Ministry of SOEs. The purpose of the initial idea of restructuring and establishing a state-owned holding company is to optimize its management. However, while its main objective is to gradually intensify its management and profitability, the government plans to restructuring SOEs must face several obstacles, one of which is related to anti-competitive law. In an Operating Holding Company, the parent company carries out business activities and controls subsidiaries. The form of Operating Holding Company run by PTPN III (Persero) as the parent company is not only to carry out its business activities but also control and supervise subsidiaries.